Telaah Kritik Atas Putusan Mahkamah Konstitusi dalam Perkara Perselisihan Hasil Pemilukada Provinsi Jawa Timur - Widodo Ekatjahjana (The Constitutional Court of the Republic of Indonesia, 2016)
Decision of Constitutional Court of Number 41/PHPU.D-VI/2008 is a controversial judicial decison in practices of Constitutional Court in Indonesia. The decison had legal basis of Law of Number 18 of 2008 that against formally with the Constitutions of 1945. Nevertheless, in fact, inconstitutional practice of the court system has taken legitimacy source of convention. It is very important for development of constitutional law enforcement in Indonesia, that the decision was not only show how the Constitutional Court improves its constitutional authorities to handle disputes of regional head election result in Indonesia, but also that was first time how the Constitutional Court has brought its justice paradigm change toward process of substantial justice and law enforcement.